Zearalenone perturbs the circadian clock and inhibits testosterone synthesis in mouse Leydig cells. Issue 3 (1st February 2021) - Zhao, Lijia; Xiao, Yaoyao; Li, Cuimei; Zhang, Jing; Zhang, Yaojia; Wu, Meina; Ma, Tiantian; Yang, Luda; Wang, Xiaoyu; Jiang, Haizhen; Li, Qian; Zhao, Hongcong; et al.
ABSTRACT: Zearalenone (ZEA), a mycotoxin, is known to impair reproductive capability by disrupting the synthesis and secretion of testosterone by Leydig cells (LCs), although the mechanism is unknown. Robust rhythmicity of circadian clock and steroidogenic genes were identified in LCs. The aim of this study was to examine whether ZEA significantly attenuated the transcription of core clock genes ( Bmal1, Dbp, Per2, and Nr1d1 ) as well as steroidogenic genes ( StAR, Hsd3b2, and Cyp11a1 ) in mouse testis Leydig cell line (TM3). Western blotting confirmed declines in BMAL1, NR1D1, and StAR protein levels. ZEA also suppressed secreted testosterone levels. In primary LCs, isolated from PER2::LUCIFERASE reporter gene knock in mice, ZEA diminished the amplitude of PER2::LUC expression, and induced a phase shift and period extension. In primary LCs, ZEA also suppressed the expression levels of core clock and steroidogenic genes, reduced protein levels of BMAL1, and decreased testosterone secretion. In vivo expression of core clock and steroidogenic genes were reduced in testes of mice exposed to ZEA for 1 week leading to decreased serum testosterone levels. In summary, data suggest that ZEA may impair testosterone synthesis through attenuation of the circadian clock in LCs culminating in reproductive dysfunction in male mammals .